Investigating the effects of students’ major and bibliographic instruction programme on library anxiety sub-scale, ‘barriers with staff’ - Abdul Karim, Noor Harun; Afaq Ansari, Novera (Malaysian Journal of Library and Information Science, 2017)
Karim, N. H. A., & Ansari, N. A. (2013). Investigating the effects of students’ major and bibliographic instruction programme on library anxiety sub-scale,‘barriers with staff’. Malaysian Journal of Library & Information Science, Vol.18, no. 3: 39-47. This study examined the effects of antecedent variables students’ major and attendance in bibliographic instruction program on the variation in library anxiety sub-scale, ‘barriers with staff’. The study employed a cross-sectional survey design using 367 students drawn randomly from a population of 8432 undergraduate students in a Malaysian institution of higher learning. The analysis of data was based on 308 usable returns. The results of running an independent sample t-test revealed that ‘barriers with staff’ did not significantly discriminate between students majoring in the human/social sciences and those majoring in the pure/applied sciences. Further, ‘barriers with staff’ was found to have significantly discriminated between students who had attended the bibliographic instruction program and those who did not attend such a program. The results of running a 2 X 2 Factorial ANOVA further supported the findings of the two independent sample t-tests in which students major was found to have no significant effect on ‘barriers with staff’ whilst attendance in bibliographic instruction program was found to have a significant effect on ‘barriers with staff’. The results of running a 2 X 2 Factorial ANOVA also revealed a statistically significant interaction effect between students’ major and attendance in bibliographic instruction program on library anxiety sub-scale, ‘barriers with staff’. The findings revealed that students majoring in the human/social sciences who had attended the bibliographic instruction program reported the lowest levels of library anxiety associated with ‘barriers with staff’ when compared to students majoring in the pure/applied sciences who had not attended such a program. This finding highlights bibliographic instruction program role as a moderating variable rather than as a typical antecedent or independent variable in the library anxiety research program.